Improvement of the decolorization of azo dyes in sequencing batch reactor by acclimation thesis - Prado, Moriel L. (2008)
The main objective of this study is to come up with an improved biological treatment system using a Sequencing Batch Reactor with a combination of anaerobic and aerobic conditions in one unit for the decolorization of wastewater containing azo dye C.I. Reactive Red 141. The reactor used a sludge that was taken directly from the Return Activated Sludge (RAS) tank of the Sewage Treatment Plant (STP) of Manila Water, Inc. Near Philcoa, Quezon City. The SBR used synthetic sugar-containing wastewater that contained varied concentrations of C.I. reactive Red 141 (100, 150, 200, 400, 600) mg/L, sucrose of 2 g/L, and 4.5 g/L NaHCO3 to keep pH at basic conditions. The biomass showed acclimation to high concentrations of CI Reactive Red 141, thus, the results showed maximum color removal of more than 70% and COD reduction was consistently more than 96%. No significant inhibitory effect was found when dye concentrations have been increased up to 600 mg/L. This investigation has shown improvement of the decolorization of azo dye in the Sequencing Batch Reactor system with alternating anaerobic-aerobic environment at basic condition.